Kebijakan Ekonomi Indonesia Ditinjau dari Konsep Dasar Ekonomi Islam - Yulia Hafizah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2005)
This paper aims to picture the Indonesia economy policy in perspective of Islamic economy concept. First, the writer describes historically the relation between economy and politic which then present the world economy systems. In Indonesia context, the system of economy which formulated was different with the other world economy system such as liberalism and mercantilism. The system economy of Indonesia, known as the Pancasila economy system stand between both of them. According to the writer, the Indonesia economy system has the same goal with the basic concept of Islamic economy that to create the social justice. The problem is that the basic concept of Indonesia economy often had the multi-faces when implemented in the reality.